208k views
5 votes
Does anyone understand how to do this?

Does anyone understand how to do this?-example-1
User Paulusm
by
4.9k points

1 Answer

4 votes

Answer:

f ( x ) = - 2x^2 + 3x + 1

Explanation:

If f ( x ) extends to → − ∞, as x→ − ∞ , provided f(x) → − ∞, as x → +∞, we can rewrite this representation as such;

− ∞ < x < ∞, while y > − ∞

Now the simplest representation of this parabola is f ( x ) = - x^2, provided it is a down - facing parabola;

If we are considering a down - facing parabola, the degree of this trinomial we should create should be even, the LCM being negative. Knowing that we can consider this equation;

Solution; f ( x ) = - 2x^2 + 3x + 1, where the degree is 2, the LCM ⇒ - 2

User Chrisinmtown
by
5.3k points